A New Bioinspired Collagen-Hydroxyapatite Bone Graft Substitute in Adult Scoliosis Surgery: Results at 3-Year Follow-Up. Issue 3 (2017) - Giorgi, Pietro; Capitani, Dario; Sprio, Simone; Sandri, Monica; Tampieri, Anna; Canella, Valentina; Nataloni, Angelo; Schirò, Giuseppe R.
Background: Spinal fusion is a common procedure used for surgical treatment of spinal deformity. In recent years, many bone graft substitutes (BGS) have been developed to provide good arthrodesis when the available autologous bone harvested from the patient is not enough. The aim of this study was to analyze the use of a new-generation composite material (RegenOss) made of Mg-hydroxyapatite nanoparticles nucleated on type I collagen to obtain long posterolateral fusion in adult scoliosis surgery. Methods: A total of 41 patients who underwent spinal fusion for the treatment of adult scoliosis were retrospectively analyzed. According to Lenke classification, visual analog scale (VAS) score and Oswestry Disability Index (ODI) score, radiographic rates of bone union were evaluated before surgery and at 6, 12 and 36 months of follow-up. Fusion was considered to be successful when criteria for Lenke grade A or B were satisfied. Patient-related risk factors were considered for the evaluation of the final outcome. Results: At 36-month follow-up, radiographic evidence of spinal fusion was present in the majority of patients (95.1%). A time-dependent statistically significant improvement was evidenced after surgery for all clinical outcomes evaluated. Based on the demographic data collected, there were no statistically significant factors determining fusion. The correction of deformity was maintained at different time points. No intraoperative or postoperative complications were recorded. Conclusions: The present study demonstrated that RegenOss can safely be used to achieve good arthrodesis when associated with autologous bone graft to obtain long spinal fusion in the treatment of adult scoliosis.